ANALISIS TINDAK TUTUR ILOKUSI DALAM FILEM SPIRITED AWAY KARYA HAYAO MIZAYAKI - Antariksawan Antariksawan; Igat Meliana (Jurnal SORA, 2021)
This research was aimed to describe the use of speech utterances conveyed by speakers to the interlocutor in Mizaki Hayao's film Spirited Away. The form of illocutionary speech acts include the types of assertive, directive, commissive, expressive and declarative speech which means complaining, reporting, pleading, ordering, asking, threatening, promising, criticizing, blaming, thanking, apologizing, praising, and giving names. The method used in this study was qualitative descriptive method. Data was collected using the technique of listening, recording and taking notes. The results of this study is the data taken from the film. From the speech data, it is then classified according to the types of speech acts and their meanings. Based on the analysis, it can be concluded that the film Sporited Away by Hayao Mizaki contains illocutionary speech acts with assertive, directive, commissive, expressive and declarative speech having the meaning of complaining, reporting, pleading, ordering, asking, threatening, promising, criticizing, blaming, thanking, apologizing, praising and naming.